Peranan Bimbingan dan Penyuluhan dalam Menanggulangi Kesulitan Belajar Siswa - Galuh Dwi Purwasih; Liyana Rakhmawati (Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2018)
The research titled "The Role of Guidance and Counseling in Overcoming Difficulties Student Learning in MIN Tunggangri Kalidawir, Tulungagung and MIN Rejoso Darul Ulum Jombang" Academic Year 2016/2017. Background of the problem: guidance and counseling service is the guidance that exist in the school is intended for students who have problems or students who need special guidance to overcome the problems faced by students themselves so that in achieving the goals of education there are no obstacles so as to achieve optimal results on some educational institutions. Guidance and counseling is actively conducting counseling process to students who are considered as students who are bundled or have problems (problems) either concerning his personality or others from his environment. And often we find in schools is the difficulty of learning in the natural by students. So that guidance and counseling is specifically handled by personnel who are considered able to provide guidance and counseling to students. Problem formulation Is there a role of guidance and counseling in tackling student learning difficulties at MIN Tunggangri Kalidawir, Tulungagung and MIN Rejoso Darul Ulum Jombang? How is the role of guidance and counseling in overcoming student learning difficulties at MIN Tunggangri Kalidawir, Tulungagung and MIN Rejoso Darul Ulum Jombang? The purpose of research to determine the efforts of counseling teachers in tackling student learning difficulties at MIN Tunggangri Kalidawir, Tulungagung and MIN Rejoso Darul Ulum Jombang. Research location at MIN Tunggangri Kalidawir, Tulungagung and MIN Rejoso Darul Ulum Jombang, (1) data source there are three stages: person, place and paper, (2) procedure Data collection through interview, observation, documentation, (3) data analysis techniques, namely: deductive data analysis and inductive data analiasis, (4) checking the validity of findings, namely: extension of participation, observation persistence, triangulation, (5) research stages , Including: introduction, stage of field work, data analysis phase. Result of research: (1) In the effort to overcome student's learning difficulties in MIN Tunggangri Kalidawir, Tulungagung and MIN Rejoso Darul Ulum Jombang, counseling guidance teacher tried to provide learning guidance service, ie through face-to-face in class with 2 hours lesson in one week, Useful, counseling advice and constructive suggestions to students, (2) In an effort to overcome student learning difficulties at MIN Tunggangri Kalidawir, Tulungagung and MIN Rejoso Darul Ulum Jombang is conducted guidance. Individually handled directly by counseling teachers, teachers try to help solve the difficulties experienced by students, (3) In handling the students' learning difficulties, guidance and counseling teachers at MIN Tunggangri Kalidawir, Tulungagung and MIN Rejoso Darul Ulum Jombang is with some handling that is : A) Calling to students who have difficulty learning to ask what makes students difficult, b) In subjects that are considered less capable of students are advised to learn it and ask additional hours to teachers of the field of study, c) Always motivate students who experience Learning difficulties are not discouraged to continue learning, d) If students experience learning difficulties due to lack of teachers books counseling guidance provides services such as counseling guidance.